2012
DOI: 10.1371/journal.pcbi.1002807
|View full text |Cite
|
Sign up to set email alerts
|

Electron Transfer Interactome of Cytochrome c

Abstract: Lying at the heart of many vital cellular processes such as photosynthesis and respiration, biological electron transfer (ET) is mediated by transient interactions among proteins that recognize multiple binding partners. Accurate description of the ET complexes – necessary for a comprehensive understanding of the cellular signaling and metabolism – is compounded by their short lifetimes and pronounced binding promiscuity. Here, we used a computational approach relying solely on the steric properties of the ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 70 publications
(122 reference statements)
1
28
0
Order By: Relevance
“…The communication maps reveal that Trp59 lies along an energy transport pathway that emerges from the heme side chains, consistent with the picosecond response time to excitation of the heme observed in the UVRR experiments [26]. However, the energy transport pathways in cytochrome c, like those for electron transfer [82], could be altered when this protein interacts with its cellular environment. However, the energy transport pathways in cytochrome c, like those for electron transfer [82], could be altered when this protein interacts with its cellular environment.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The communication maps reveal that Trp59 lies along an energy transport pathway that emerges from the heme side chains, consistent with the picosecond response time to excitation of the heme observed in the UVRR experiments [26]. However, the energy transport pathways in cytochrome c, like those for electron transfer [82], could be altered when this protein interacts with its cellular environment. However, the energy transport pathways in cytochrome c, like those for electron transfer [82], could be altered when this protein interacts with its cellular environment.…”
Section: Discussionsupporting
confidence: 64%
“…. Here, we use the normalization procedure due to Dragt and Finn [ 82 ], which is classifi ed as format 2a in [ 12 ]. , q n ) be coordinates in an n -dimensional Hamiltonian system and p = (p 1 , .…”
Section: Non-blow-up Regions Of Lcpt For N -Dimensionalmentioning
confidence: 99%
“…Indeed, molecular docking simulations have suggested that flavonoids can interact with Cyt c at different sites or in different modes, but all of them share binding to basic residues, namely, Lys79, Arg38, Lys39, Lys13 and His18, consistent with the importance of electrostatic forces and pH in the reduction of Cyt c . Moreover, interaction of flavonoids with Lys79 and vicinal basic residues of Cyt c may further potentiate electronic capture by the heme , which could explain the high reducing efficiency of flavonoids like quercetin, kaempferol and cyanidin. Furthermore, a cluster of Lys and His residues at the entrance of the heme crevice constitutes the L site implicated in Cyt c interaction with acidic lipids, with p K a values 6.5–7 , which correlates with the pH‐dependence of the reduction rates by quercetin and kaempferol found in our work.…”
Section: Discussionmentioning
confidence: 93%
“…26 Isoelectric point (pI) of Cyt c is 10.02-10.5 and the abundant charged lysine residues around the heme edge 27 is responsible for rapid interprotein electron transfer due to electrostatic steering. 28 Cyt c at neutral pH has a net positively charge causing its stickiness and this also facilitates some strong and unspecic interactions. 29 It can act as surfactant in reverse micellar solution.…”
Section: Introductionmentioning
confidence: 99%